2014
DOI: 10.1007/s00268-014-2566-3
|View full text |Cite
|
Sign up to set email alerts
|

Tragic Knowledge: Truth Telling and the Maintenance of Hope in Surgery

Abstract: Surgeons often are faced with the challenge of balancing truth telling and the maintenance of hope in the setting of a poor prognosis. This ethical dilemma is informed by conflicting appeals to principles of autonomy and nonmaleficence, where a patient's right to be told important medical information must be weighed against the potential harm that may result from the knowledge of an unfavourable diagnosis. Truth telling in surgery raises questions on the nature of truth itself, how much information ought to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…This is an important gap in knowledge considering that family plays an important role in Asian medical cultures 20,24,25 and many health care providers have indicated that predicaments in their truth-telling practice are mainly family related. 13,17,25,[37][38][39] This issue underscores the importance of our findings on Taiwanese family members' truth-telling preferences.…”
Section: Item-wise Analysis Of Truth-telling Scale Scoresmentioning
confidence: 62%
See 1 more Smart Citation
“…This is an important gap in knowledge considering that family plays an important role in Asian medical cultures 20,24,25 and many health care providers have indicated that predicaments in their truth-telling practice are mainly family related. 13,17,25,[37][38][39] This issue underscores the importance of our findings on Taiwanese family members' truth-telling preferences.…”
Section: Item-wise Analysis Of Truth-telling Scale Scoresmentioning
confidence: 62%
“…Although the importance of family has been emphasized during the truth‐telling process, none of these studies used validated instruments to investigate families' truth‐telling preferences. This is an important gap in knowledge considering that family plays an important role in Asian medical cultures and many health care providers have indicated that predicaments in their truth‐telling practice are mainly family related . This issue underscores the importance of our findings on Taiwanese family members' truth‐telling preferences.…”
Section: Discussionmentioning
confidence: 79%
“…While technological advancements have improved diagnostic and prognostic accuracy in emergency care, better accuracy does not necessarily assuage the difficulty of balancing truth and hope. 6 All of this is particularly challenging when communicating clinical equipoise, a situation where two or more treatment options exist but neither is clearly superior. Providers need to communicate uncertainty and adequate information on disease mechanism, estimation of prognosis, and risks and benefits of each treatment option for the patient to make an informed decision.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians and nurses still struggle to find the best way to tell bad news without causing undue harm to the patients. 3,6…”
Section: Introductionmentioning
confidence: 99%